Theorizing Precommitment in European Integration: Mending the Constraints of Ulysses - Lavdas, Kostas A. (2012)
Abstract: The paper engages with the debate on Europe’s prospects by using Elster’s constraint theory to develop a model of precommitment in a context of diffuse reciprocity as a condition for interactive Europeanization. The current crisis constitutes a juncture in EU development, calling for a reassessment of the established views on Europe’s experiment. Europeanization emerges as a critical field for testing integration. The paper suggests a framework for the analysis of Europeanization which rests on two approaches: (a) the evolution of mixed and diffuse reciprocity (‘beyond tit-for-tat’) and (b) the development of precommitment and selfimposed constraints (‘Ulysses and the sirens’). It is argued that, given enormous challenges for the consolidation of precommitmnent due to a combination of economic strains and political gaps in steering, further evolution of advanced forms of reciprocity in Europe would require new goals, enhanced normative and value contents and increased political and